2015
DOI: 10.1017/s0007114515002366
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D supplementation on selected inflammatory biomarkers in older adults: a secondary analysis of data from a randomised, placebo-controlled trial

Abstract: Observational studies have suggested that 25-hydroxyvitamin D (25(OH)D) levels are associated with inflammatory markers. Most trials reporting significant associations between vitamin D intake and inflammatory markers used specific patient groups. Thus, we aimed to determine the effect of supplementary vitamin D using secondary data from a population-based, randomised, placebo-controlled, doubleblind trial (Pilot D-Health trial 2010/0423). Participants were 60-to 84-year-old residents of one of the four easter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 50 publications
(91 reference statements)
5
13
1
Order By: Relevance
“…Taking 50000 IU-vitamin D for 8 weeks has been recommended for the treatment of vitamin D deficiency [26]. Similar results were observed for the effect of vitamin D supplementation on serum 25 OH) vitamin D in previous studies [41][42][43].…”
Section: Discussionsupporting
confidence: 76%
“…Taking 50000 IU-vitamin D for 8 weeks has been recommended for the treatment of vitamin D deficiency [26]. Similar results were observed for the effect of vitamin D supplementation on serum 25 OH) vitamin D in previous studies [41][42][43].…”
Section: Discussionsupporting
confidence: 76%
“…Exercise training (Singh and Newman 2011), and certain isolated nutritional supplements such as whey protein (de Aguilar<Nascimento et al 2011;Sugawara et al 2012), creatine (Santos et al 2004;Bassit et al 2008), vitamin D/calcium (Bjorkman et al 2009;Waterhouse et al 2015), and omega<3 polyunsaturated fatty acids (n<3 PUFA) (Zhao et al 2009;Tartibian et al 2011), have previously been shown to reduce circulating concentrations of pro<inflammatory cytokines. Recently we demonstrated that a broad spectrum nutritional supplement (which included these aforementioned ingredients: creatine, whey, vitamin D, calcium, and n<3 PUFA) improved strength and lean tissue mass in a group of healthy older men versus a nutrition control (Bell et al 2017).…”
Section: %And #$' %#mentioning
confidence: 99%
“…Low<grade sterile inflammation due to increased oxidative stress (Singh and Newman 2011) and/or central (particularly visceral) adiposity (Ryan 2000;Singh and Newman 2011) has been suggested as a mechanism by which cardiometabolic disease develops in older age, and is therefore a worthwhile target for intervention. Previous studies have investigated the independent ability of whey protein (de Aguilar<Nascimento et al 2011;Sugawara et al 2012), creatine (Santos et al 2004;Bassit et al 2008), vitamin D (Bjorkman et al 2009;Waterhouse et al 2015), and n<3…”
Section: $% ' %#mentioning
confidence: 99%
“…Evidence from an interventional study investigating the effect of vitamin D supplementation on selected inflammatory biomarkers in older adults using secondary data from a randomised, placebo-controlled trial found little evidence of an effect of vitamin D supplementation on cytokine or adipokine levels, with the possible exception of IL-6 ( 35 ) . A recent study ( 36 ) , investigating the association between serum 25(OH)D and CRP and a potential causal effect by using genetic variants in bi-directional Mendelian randomisation analysis, in the Rotterdam Study, a prospective population-based cohort, showed that serum vitamin D was inversely associated with CRP.…”
Section: Discussionmentioning
confidence: 99%